Extruded sorghum and Bambara groundnuts : influence of in-barrel moisture conditions on functional and nutritional characteristics - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.